1995
DOI: 10.2136/sssaj1995.03615995005900030013x
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis of Heat Pulse Method for Measuring Soil Heat Capacity, Diffusivity, and Conductivity

Abstract: A dual‐probe heat pulse (DPHP) method was developed recently that allows for the simultaneous, automated measurement of soil thermal diffusivity (κ), volumetric heat capacity (ρc), and thermal conductivity (λ). Estimation of thermal properties is based on theory for the conduction of heat away from an infinite line source (ILS) that is heated for a short period of time. In this study, we examined possible sources of error in the use of the ILS theory by comparing it with other models that explicitly account fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 0 publications
2
99
0
1
Order By: Relevance
“…The l of the soil is calculated based on temperature measurements and knowledge of the heat generated (~22.3 W m −1 ) during heating (1 min) and cooling (1 min) cycles (Decagon Devices, 2014). The calculations derive from a dual needle algorithm based on the line heat source analysis (Carslaw and Jaeger, 1959;Abramowitz and Stegun, 1972;Kluitenberg et al, 1993Kluitenberg et al, , 1995Bristow et al, 1994).…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…The l of the soil is calculated based on temperature measurements and knowledge of the heat generated (~22.3 W m −1 ) during heating (1 min) and cooling (1 min) cycles (Decagon Devices, 2014). The calculations derive from a dual needle algorithm based on the line heat source analysis (Carslaw and Jaeger, 1959;Abramowitz and Stegun, 1972;Kluitenberg et al, 1993Kluitenberg et al, , 1995Bristow et al, 1994).…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…The volumetric specific heat is then determined from these parameters. The dual-needle algorithm was presented by Kluitenberg et al [18], and details about the design and working of the KD2-Pro device can be found in the operator's manual [19]. The uncertainty in the measurement of thermal conductivity and thermal diffusivity was calculated from repeated tests to be ±10%, and the uncertainty in the calculation of the specific heat was ±14%.…”
Section: Measurement Of Thermal Propertiesmentioning
confidence: 99%
“…The schematic view of a thermo-FDR sensor is shown in Fig. 2. Experiment Bristow et al (1994), Kluitenberg et al (1995), Noborio et al (1996), and Ren et al (1999Ren et al ( , 2003bRen et al ( , 2005 presented accurate measurements of soil thermal properties with 6-mm tube-to-tube spacing heat pulse sensors. Thus, the heat pulse design selected for the thermo-FDR sensor has already been verified in the literature.…”
Section: Sensor Designmentioning
confidence: 99%